Description of Rhinobatos ranongensis sp. nov. (Rhinopristiformes: Rhinobatidae) from the Andaman Sea and Bay of Bengal with a review of its northern Indian Ocean congeners - Last, Peter R.; Séret, Bernard; Naylor, Gavin J.p. (Zootaxa, 2019)
A new species of guitarfish, Rhinobatos ranongensis sp. nov., is described from 5 preserved specimens, and images and tissue samples of additional material, collected from the Andaman Sea and Bay of Bengal. This species co-occurs in the eastern sector of the northern Indian Ocean with two poorly defined congeners, R. annandalei Norman and R. lionotus Norman, which have been misidentified and confused with Indo-Pacific congeners since they were first described in 1926. Norman’s species are rediagnosed based on limited new material and a re-examination of the types. In the western sector of the northern Indian Ocean, Rhinobatos annandalei has been confused in recent literature with the sympatric R. punctifer Compagno and Randall, which is represented by four primary colour morphs, including a white-spotted colour morph resembling R. annandalei. Rhinobatos punctifer also displays strong intraspecific variability and sexual dimorphism in some body dimensions. These four species of Rhinobatos have unique MtDna sequences and belong to a clade of Indo-West Pacific species that are morphologically similar. Despite the relatively small numbers of specimens available for investigation, these species exhibit some clear differences in body proportions, meristics and squamation. Rhinobatos ranongensis sp. nov. differs from its northern Indian Ocean congeners through a combination of a relatively narrow disc and mouth, high vertebral count, long snout, low dorsal fins, and being largely plain coloured. A new lectotype and a paralectotype are designated for the syntypes of R. annandalei, and the four primary colour forms of R. punctifer, the plain, white-spotted and ocellated morphs, are described and the three nominal species rediagnosed. A key is provided to the four known members of the genus in the northern Indian Ocean.